Serological cross-reactivity of environmental Escherichia coli strains with Shigella-specific antisera - Azmuda, Nafisa; Bilkis, Rabeya; Akter, Humaira; Begum, Anowara; Khan, Sirajul Islam; Birkeland, Nils Kåre (Bangladesh Journal of Microbiology, 2018)
Many bacteria of clinical and environmental origin show evidence of sharing common surface antigens. The present study aimed for isolation of Escherichia coli strains that were serologically cross-reactive with Shigella species from freshwater ecosystems in Bangladesh by conventional cultural methods. Among twenty eight isolates, two isolates, termed 12(35) and 6(50) showed cross-reactivity with four polyvalent serogroup-specific Shigella antisera using slide agglutination assay. The isolates were identified and charcterized by cultural and biochemical properties and Western blot analysis. The isolates showed typical Escherichia coli cell morphology and cultural and biochemical properties and were identified as Escherichia coli by API 20E tests. Western blot analysis confirmed the isolates as cross-reactive with all the four group-specific Shigella antisera due to presence of immunogenic proteins and LPS. One of the isolates also showed cross-reactivity with multiple type-specific Shigella boydii antisera (monovalent) because of immunogenic proteins. Both the isolates were identified as nonpathogenic due to absence of virulence marker genes of diarrheagenic E. coli variants.This study revealed that a number of bacteria present in the environment could share important Shigella species surface antigens. Naturally occurring nonpathogenic environmental bacteria expressing surface antigens specific for certain types of Shigella could be a good choice for vaccine candidates against shigellosis. Bangladesh J Microbiol, Volume 33, Number 1-2, June-Dec 2016, pp 29-33